Effectiveness of tuberculosis preventive treatment on disease incidence among people living with HIV/AIDS: A systematic review and meta-analysis - José Nildo de Barros Silva Júnior; Gilberto da Cruz Leal; Quézia Rosa Ferreira; Licia Kellen de Almeida Andrade; Jaqueline Garcia de Almeida Ballestero; Victor Santana Santos; Júlia M.a Pescarini; Anete Trajman; Denise Arakaki-Sanchez; Patricia Bartholomay; Rubia Laine de Paula Andrade; Daniele Pelissari; et al. (PLoS ONE, 2025)
Background Clinical trials have shown the protective efficacy of tuberculosis preventive treatment (TPT) for averting disease and death from tuberculosis among people living with HIV/AIDS (PLHIV). TPT has been recommended for PLHIV since the 1980s. However, tuberculosis is still the first cause of death in PLHIV. Objective We aimed to summarize the evidence related to the real-world effectiveness of TPT on tuberculosis incidence among PLHIV. Method This is a systematic review and meta-analysis of observational cohort studies. The search was carried out in PubMed (via MEDLINE), Embase, LILACS, Scopus and Web of Science databases. Free and controlled vocabulary was used for the searches, with no restrictions on language or publication period. Studies reporting hazard ratios (HR) for tuberculosis incidence among PLHIV who received TPT were pooled using random-effects meta-analysis models. Meta-regression was performed to assess whether study-level characteristics accounted for heterogeneity, as evaluated by Cochran’s I² statistic. Study quality was appraised using the Newcastle-Ottawa Scale. This study was registered with PROSPERO (CRD42024586273). Results Among 8,330 screened studies, 34 were included, with nine contributing to the meta-analysis. TPT was associated with a 63% reduction in tuberculosis incidence risk (HR = 0.37, 95% CI: 0.28–0.48; I² = 43%). Children exhibited consistent stronger protection (82% risk reduction, HR = 0.18, 0.09–0.37; I² = 0%) than adults (56% reduction, HR = 0.44, 0.37–0.53; I² = 21%). Conclusion In real world conditions, TPT significantly and substantially reduces tuberculosis incidence in PLHIV, with consistent evidence of stronger protective effects in children. Despite some heterogeneity among adult studies, the pooled evidence confirms the protective effectiveness previously observed in clinical trials. These findings reinforce the global recommendation for broad implementation of TPT among PLHIV.